Effectiveness of digital healthcare to improve clinical outcomes in discharged patients with coronary artery disease - Lanshu Yang; Zuoxiang Wang; Sheng Zhao; Mengyuan Liu; Yalin Zhu; Fenghuan Hu; Xiaojin Gao; Yongjian Wu (npj Digital Medicine)
Abstract Post-discharge management of coronary artery disease (CAD) remains clinically challenging, with digital healthcare’s efficacy underexplored. This study analyzed 16,797 CAD patients enrolled in the HeartMed Digital Management System (June 2018–September 2022), comparing outcomes between a digital management (DM, n = 4,713) and conventional management (CM, n = 12,084) cohort over 12 months. Cox models adjusted for confounders revealed significantly reduced all-cause mortality in the DM group (1.6% vs. 2.7%; HR 0.58, 95% CI 0.45–0.75, p < 0.001) and lower risks for major adverse cardiovascular events (MACCE: 6.4% vs. 9.2%; HR 0.67, 0.59–0.77, p < 0.001), cardiovascular death (HR 0.70, 0.51–0.95), myocardial infarction (HR 0.38, 0.29–0.50), recurrent angina (HR 0.75, 0.65–0.87), revascularization (HR 0.84, 0.71–0.99), and readmissions (HR 0.76, 0.68–0.84) (p < 0.05 for all). Digital healthcare demonstrates superior post-discharge optimization of CAD outcomes, significantly attenuating mortality and morbidity.